"Driving the devil away": qualitative insights into miraculous cures for AIDS in a rural Tanzanian ward - María Roura; Ray Nsigaye; Benjamin Nhandi; Joyce Wamoyi; Joanna Busza; Mark Urassa; Jim Todd; Basia Żaba (2010)
The role of religious beliefs in the prevention of HIV and attitudes towards the infected has received considerable attention. However, little research has been conducted on Faith Leaders' (FLs) perceptions of antiretroviral therapy (ART) in the developing world. This study investigated FLs' attitudes towards different HIV treatment options (traditional, medical and spiritual) available in a rural Tanzanian ward. Qualitative interviews were conducted with 25 FLs purposively selected to account for all the denominations present in the area. Data was organised into themes using the software package NVIVO-7. The field work guidelines were tailored as new topics emerged and additional codes progressively added to the coding frame. Traditional healers (THs) and FLs were often reported as antagonists but duality prevailed and many FLs simultaneously believed in traditional healing. Inter-denomination mobility was high and guided by pragmatism. Praying for the sick was a common practice and over one third of respondents said that prayer could cure HIV. Being HIV-positive was often seen as "a punishment from God" and a consequence of sin. As sinning could result from "the work of Satan", forgiveness was possible, and a "reconciliation with God" deemed as essential for a favourable remission of the disease. Several FLs believed that "evil spirits" inflicted through witchcraft could cause the disease and claimed that they could cast "demons" away. While prayers could potentially cure HIV "completely", ART use was generally not discouraged because God had "only a part to play". The perceived potential superiority of spiritual options could however lead some users to interrupt treatment. The roll-out of ART is taking place in a context in which the new drugs are competing with a diversity of existing options. As long as the complementarities of prayers and ART are not clearly and explicitly stated by FLs, spiritual options may be interpreted as a superior alternative and contribute to hampering adherence to ART. In contexts where ambivalent attitudes towards the new drugs prevail, enhancing FLs understanding of ART's strengths and pitfalls is an essential step to engage them as active partners in ART scale-up programs.